Transition From Original Printing Pictures To 3D Printing Technology - Tingir, Merve; Tarlakazan, Elif (Ordu University, 2022)
The original print painting has survived to the present day by changing with the progress of societies and time in the historical process. The development of technology has led to the use of the art of printmaking only for individual or educational purposes in schools. Today, 3D printing production techniques emerge as a new field in both design and production areas. Thanks to the convenience it offers, an alternative art creation tool emerges for designers. Using 3D printing with different disciplines, it creates diversity in the name of design and art. Thanks to the renewed technological developments, it contributes to its development by taking a new field into its sphere of influence every day. In the study, historical and general information about the art of printmaking is included, and the transition processes to 3D printing technology are discussed and compared. In addition, the transition processes and applications to 3D printing systems were examined. Qualitative research method will be used in the research. By making a literature review, the studies on the subject will be discussed and interpreted. This method covers the comparison of original print painting and 3D printing technology by referring to the point they have reached.
Keywords: Özgün baskı resim; D baskı; Dijital baskı; Teknoloji; Tasarım; Keywords: Original print; D printing; Digital printing; Technology; DesignGiriş